POLITICAL ELITES AND THE CHALLENGES OF NATIONAL DEVELOPMENT: THE NIGERIA EXPERIENCE - Bariledum, Kia; Serebe S., Vurasi (European Scientific Journal, ESJ, 2013)
Political elites and the challenges of national development: the Nigeria experience explains the countryâ€™s development challenges in relations to problems associated with eliteâ€™s ethnification of political process that undoubtedly affects public policy formation and implementations in Nigeria. In this case we have the syndrome of â€œwe want our man in national politics.â€ This practice negates meritocracy and sound developmental policy. Under this condition, national development is unattainable. To achieve national development, the government should actively encourage national integration and eschew discrimination on the ground of place of birth, tribe, religion, sex, language and political party affiliation.